ÁGUA SUBTERRÂNEA NA REGIÃO METROPOLITANA DE SÃO PAULO ATUAÇÃO DA SABESP - Tinoco, M. P.; Pannuti, E. L.; Mohallem, R.; Sanchez, M. G.; Kosmiskas, J`. P.; Terada, M. (Águas Subterrâneas, 1990)
INDISPONÍVEL